Molecularly Imprinted Polymers for the Detection of Chlorpyrifos (an Organophosphate Pesticide) - Rafia Altaf; Zafran Ullah; Daniel Amoako Darko; Asif Iqbal; Muhammad Shahzeb Khan; Muhammad Asif (Universitas Pendidikan Indonesia (UPI), 2022)
Chlorpyrifos belongs to an organophosphate pesticides group that is frequently used to increase the yield of crops by controlling plant and pests-related diseases. Chlorpyrifos contaminates the environment and cause diseases to the human population. Molecularly imprinting technology lead to the development of molecularly imprinted polymers having templated oriented cavities with high selectivity, sensitivity, stability, and portability. Our review article aims to provide a collective study related to pesticides detection through molecularly imprinted polymers with existed constraints and necessary potential facets are discussed.